Cholesterol transfer at the plasma membrane. (November 2019) - Axmann, Markus; Strobl, Witta Monika; Plochberger, Birgit; Stangl, Herbert
Abstract: Cholesterol homeostasis is of central importance for life. Therefore, cells have developed a divergent set of pathways to meet their cholesterol needs. In this review, we focus on the direct transfer of cholesterol from lipoprotein particles to the cell membrane. More molecular details on the transfer of lipoprotein-derived lipids were gained by recent studies using phospholipid bilayers. While amphiphilic lipids are transferred right after contact of the lipoprotein particle with the membrane, the transfer of core lipids is restricted. Amphiphilic lipid transfer gains special importance in genetic diseases impairing lipoprotein metabolism like familial hypercholesterolemia. Taken together, these data indicate that there is a constant exchange of amphiphilic lipids between lipoprotein particles and the cell membrane. Graphical abstract: Image 1 Highlights: Free cholesterol transfer from lipoprotein particles to the plasma membrane occurs in mammals. Amphiphilic lipid transfer occurs upon contact of lipoprotein particles to the plasma membrane. Both transfer mechanisms are driven by a concentration gradient. They are independent of the apolipoprotein/protein composition of the lipoprotein particle. Close proximity of lipoprotein particles to the membrane yields immediate transfer of cholesterol.